The paleoecological and paleodietary significance of edible land snails (Helix sp.) across the Pleistocene-Holocene transition on the eastern Adriatic coast - Rizner, Mia; Miracle, Preston; Vukosavljević, Nikola (2009)
This paper examines the palaeoecological and paleodietary significance of edible land snails from several different points of view: ethno-archaeological, nutritional, experimental and theoretical, based on the study of assemblages from the Pupićina cave (north-east Istria, Croatia). Several lines of evidence show that large land snails (Helix sp.) were brought on site for food. At the local level, ethnoarchaeological and taphonomic studies reveal the possible ways in which snails were prepared for eating. At a broader scale this pattern of diversifying the food supply is well known in the circum-Mediterranean region and correlates with significant environmental changes (e.g. flooding of the Adriatic plain).
Projekt MZOS
ENG